2023
DOI: 10.3390/agronomy13102468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Application of Organic Fertilizer on the Growth and Yield of Pakchoi under Different Irrigation Water Types

Shudong Lin,
Chunhong Wang,
Qingyuan Lei
et al.

Abstract: The long-term utilization of inorganic fertilizers in pakchoi cultivation can result in increased nitrate levels, potentially posing health risks to human consumers. For this study, we investigated the efficacy of organic fertilizers as a promising alternative for enhancing soil structure, improving fertility, and increasing the yield of pakchoi. A two-year field trial was conducted from 2022 to 2023 to examine the effects of the combined application of organic fertilizer on the growth and yield of pakchoi. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Fertilizer application influenced leaf area, collar diameter, fruit mass, and yield. Previous studies have shown that organic and mineral fertilizers accelerate the increase in leaf area [19]. The highest averages for the above agromorphological parameters were obtained using the biofertilizer Retone and the mineral fertilizer NPK.…”
Section: Discussionmentioning
confidence: 81%
“…Fertilizer application influenced leaf area, collar diameter, fruit mass, and yield. Previous studies have shown that organic and mineral fertilizers accelerate the increase in leaf area [19]. The highest averages for the above agromorphological parameters were obtained using the biofertilizer Retone and the mineral fertilizer NPK.…”
Section: Discussionmentioning
confidence: 81%
“…25 Other investigations have revealed the significant effects of magnetized-ionized water irrigation on pak choi, eggplants, and cotton. 45,[60][61][62][63] Olant height, stem diameter, leaf number, and crop yield were notably augmented due to this treatment. This study has revealed that magnetized-ionized water irrigation enhanced key parameters including H, LAI, DM, and SPAD during the cotton seedling period.…”
Section: Effects Of Magnetized-ionized Water Irrigation On Crop Growthmentioning
confidence: 95%
“…The leaves and stem of the plants were placed into an oven at 105 °C for 30 min and then dried at 75 °C to a constant weight, where they were subsequently weighed. The dry matter accumulation was determined as follows: 45 DM=DMp×P …”
Section: Methodsmentioning
confidence: 99%
“…The yield of pakchoi at maturity is quantified based on its fresh weight. Yield calculation, as per Equation (1), involves harvesting and weighing all pakchoi plants from each plot [29]. The soluble sugar (SS, g/kg) and soluble protein (SP, g/kg) content in pakchoi were measured using the anthrone and Coomassie Brilliant Blue UV spectrophotometry methods, respectively (Shimadzu, Kyoto, Japan, UV-1900i) [30,31].…”
Section: Measurements Of Pakchoi Samplesmentioning
confidence: 99%
“…Under brackish water irrigation, optimal values for yield, SS, and SP were obtained at organic fertilizer application rates of 76.18, 56.91, 40.79 kg/ha, reaching peaks of 47,127 kg/ha for yield, 32.97 g/kg for SS, and 4.46 g/kg for SP, respectively. This pattern indicates that achieving optimal yield and quality in brackish water conditions requires a higher application of organic fertilizer [29,31]. This study examines the effects of organic fertilizer on the photosynthetic attributes and yield of pakchoi under the conditions of both fresh water and brackish water irrigation.…”
Section: Relationship Between Photosynthetic Characteristics and Yiel...mentioning
confidence: 99%